Diagnosis and molecular characterization of Anaplasma platys in dog patients in Yogyakarta area, Indonesia - Muh. Disna Faizal; Aris Haryanto; Ida Tjahajati (Universitas Gadjah Mada, 2019)
Anaplasma platys is a tick-borne, Gram-negative bacterium that causes anaplasmosis, a companion vector-borne disease impacting dogs. Information on this disease remains limited in Indonesia. Its symptoms are not specific, so molecular analysis is required for a rapid and accurate diagnosis. GroEL is an essential gene commonly used for classification and species identification of many groups of bacteria, including Anaplasma spp. In this study, a molecular diagnosis of anaplasmosis based on the groEL gene sequence was conducted using PCR. In addition, the genetic diversity of Anaplasma platys in infected dogs was determined. Blood samples were collected from 51 dogs suspected of anaplasmosis from Prof. Dr. Soeparwi Animal Hospital, animal clinics, and pet shops in the Yogyakarta area, Indonesia, based on anamnesis, histories of tick infestations, and clinical symptom examinations. DNA extraction and PCR targeting the groEL gene were performed, followed by sequencing. Phylogenetic tree analysis and construction were carried out using the BLAST and MEGA programs. Positive PCR sample results (amplicon length of 624 bp) were found in 6 of 51 dogs. Samples A1 (KHJ/C2), A2 (KHJ/A2), A3 (KSK/L), A4 (KHJ/L), and A5 (KNP/M2) had close ties to Anaplasma platys (AF478129.1) from GenBank. Phylogenetic analysis showed a very high homology value (100%) and bootstrap value of 100%. It can be concluded that there was no genetic diversity in the Anaplasma platys found in infected dogs in the Yogyakarta area.